(untitled) (UNED Research Journal, 2014)
ABSTRACT: Sisorid catfish of the genus Glyptothorax are widely distributed, with as many as 40 nominal species reported from India, where they typically inhabit fast-flowing hill streams and faster flowing stretches of larger rivers and streams. We recorded new biogeographical distribution of three species of Glyptothorax from the tributaries of northern plains in the Ganges basin. The specimens were collected during experimental fishing for biodiversity studies using cast nets (2010-2012). While G. conirostris were collected from the Ganges canal, G. cavia and G. telchitta were captured from the river Gomti. Previous descriptions were based on preserved specimens; we present diagnostic features and an illustrated redescription based on fresh specimens. KEY WORDS: new distribution, Glyptothorax conirostris, G. telchitta, G. cavia, tributary,Ganges basin, India